2010
DOI: 10.2478/v10003-010-0021-5
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Dating of the Sediments from a Buried Channel Loop in Fatehabad Area, Haryana: Insight into Vedic Saraswati River and its Environment

Abstract: Geomorphology and sedimentary composition of an archeologically important palaeochannel segment of the Vedic Saraswati River in northwestern Haryana have been evaluated and its temporal relation with the surrounding upland examined with the help of OSL dating. Sediment composition and OSL ages suggest that the channel received enough water supply between 5.9 and 4.3 ka ago, and even before. Several lakes and ponds had developed during this period in the surrounding areas. It was a wet phase in this area as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…3). The OSL ages of sand dunes in this study are fairly consistent with the results reported by Singhvi et al (1982), Chawla et al (1992), Juyal et al (2003), and Saini and Mujtaba (2010). Results show that dunebuilding activity in the Thar Desert had already started at ca.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…3). The OSL ages of sand dunes in this study are fairly consistent with the results reported by Singhvi et al (1982), Chawla et al (1992), Juyal et al (2003), and Saini and Mujtaba (2010). Results show that dunebuilding activity in the Thar Desert had already started at ca.…”
Section: Resultssupporting
confidence: 82%
“…During 12-8 ka, aeolian deposition was subdued because of enhanced moisture. Saini and Mujtaba (2010), used optically stimulated luminescence (OSL) dating based on the single aliquot regenerative-dose (SAR) protocol (Murray and Wintle, 2000). They found that the palaeochannel identified between Fatehabad and Hosanga, in the northwestern part of Haryana, received sufficient water supplies between 5.9 ka and 4.3 ka.…”
Section: Introductionmentioning
confidence: 99%
“…Similar, very fine-grained infill was also documented by Saini et al 45, 46 along a section of the Ghaggar–Hakra palaeochannel. Thus, despite the diversion of the Sutlej, some fluvial flow and deposition of fine sediment continued in the topographic low formed by the relict valley.…”
Section: Discussionsupporting
confidence: 84%
“…The degree of bleaching is evaluable from histograms as shown in Fig. 2 for each measured sample (Olley et al, 1998;Murray and Olley, 2002;Goedicke, 2003;Saini and Mujtaba, 2010). The individual ED values were entered into bins of 0.1 Gy and so the frequency distributions were obtained.…”
Section: Ed Determination and Partial Bleaching Testmentioning
confidence: 99%
“…The thermal transfer effects were studied through the behaviour of ED and recovery test values against preheating temperature (Choi et al, 2003;Thomas et al, 2003;Kiyak and Canel, 2006). In order to investigate the degree of bleaching, the ED frequency distributions (Olley et al, 1998;Murray and Olley, 2002;Goedicke, 2003;Saini and Mujtaba, 2010) and time of bleaching in the easy-to-bleach OSL traps (Agersnap Larsen et al, 2000) were studied. The OSL ages were obtained using the Central Age Model (CAM) (Galbraith et al, 1999) and the results were compared with TL dating from bricks associated with the mortars.…”
Section: Introductionmentioning
confidence: 99%